2002
DOI: 10.1097/00008390-200204000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Melanin affinity of N-(2-diethylaminoethyl)-4-iodobenzamide, an effective melanoma imaging agent

Abstract: The cellular uptake and incorporation in macromolecules of iodine-125 labelled N-(2-diethylaminoethyl)-4-iodobenzamide ([125I]BZA), a melanoma imaging agent, was studied using human melanoma cells M3Dau (amelanotic) and M4Beu (melanotic). The interaction between [125I]BZA and synthetic melanin was examined in various conditions of incubation. The results showed that uptake was high only for M4Beu, whereas the incorporation in trichloroacetic acid-precipitable proteins was very low for both model cell lines, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…MEL037 has biologic activity that may result from 3 potential mechanisms-that is, melanin binding (20), melanin synthesis (21), or affinity to the s-receptors that are highly expressed in melanoma cells (22) and tumor tissues (23). Depending on the molecular structure, one of these mechanisms or a combination of mechanisms can take place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MEL037 has biologic activity that may result from 3 potential mechanisms-that is, melanin binding (20), melanin synthesis (21), or affinity to the s-receptors that are highly expressed in melanoma cells (22) and tumor tissues (23). Depending on the molecular structure, one of these mechanisms or a combination of mechanisms can take place.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of aminoalkyl-iodobenzamides indicated that the uptake is related to the melanin content of cells, and pharmacologic studies demonstrated that it is not s-receptor dependent (8,24,26). Experiments in cell culture showed that uptake of 123 I-BZA was rapid and high in B16 or M4Beu melanotic cells and was low in M3Dau amelanotic cells (20). Using the secondary ion mass spectrometry technique, the localization of BZA was demonstrated to be intracytoplasmic in tumoral melanocytes and in the pigmented structures of the skin and the eye and was unambiguously proven to be within melanosomes excluding a specific binding to membrane s-receptors (27).…”
Section: Discussionmentioning
confidence: 99%
“…To test the affinity of IBgBZ for melanoma tumors, a tissue distribution study was first conducted in C57BL/6 male mice bearing B16 murine melanoma xenograft. It is the standard model used in our laboratory to evaluate tumor affinity for melanoma-imaging agents Labarre et al, 2002). In addition, it allows formation of the pulmonary colonies Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…To validate our targeting strategy, two melanoma models were used. For biodisposition and SIMS studies, the B16 murine melanoma model validated by our previous work on melanoma-imaging agents was used Labarre et al, 2002;Guerquin-Kern et al, 2004). Because AGT levels in the B16 murine melanoma cell line were very low, pharmacological evaluation was performed using M4Beu human melanoma, a model that exhibited a high AGT activity and was chemoresistant to O 6 -alkylating agents such as CENUs (Cussac et al, 1994a;Mounetou et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation